Multicenter validation of spin‐density projection‐assisted R2‐MRI for the noninvasive measurement of liver iron concentration. Issue 6 (2nd July 2013) - St Pierre, Tim G.; El‐Beshlawy, Amal; Elalfy, Mohsen; Al Jefri, Abdullah; Al Zir, Kusai; Daar, Shahina; Habr, Dany; Kriemler‐Krahn, Ulrike; Taher, Ali
<x xml:space="preserve">Abstract</x> Purpose Magnetic resonance imaging (MRI)‐based techniques for assessing liver iron concentration (LIC) have been limited by single scanner calibration against biopsy. Here, the calibration of spin‐density projection‐assisted (SDPA) R2‐MRI (FerriScan®) in iron‐overloaded β‐thalassemia patients treated with the iron chelator, deferasirox, for 12 months is validated. Methods SDPA R2‐MRI measurements and percutaneous needle liver biopsy samples were obtained from a subgroup of patients (n = 233) from the ESCALATOR trial. Five different makes and models of scanner were used in the study. Results LIC, derived from mean of MRI‐ and biopsy‐derived values, ranged from 0.7 to 50.1 mg Fe/g dry weight. Mean fractional differences between SDPA R2‐MRI‐ and biopsy‐measured LIC were not significantly different from zero. They were also not significantly different from zero when categorized for each of the Ishak stages of fibrosis and grades of necroinflammation, for subjects aged 3 to <8 versus ≥8 years, or for each scanner model. Upper and lower 95% limits of agreement between SDPA R2‐MRI and biopsy LIC measurements were 74 and −71%. Conclusion The calibration curve appears independent of scanner type, patient age, stage of liver fibrosis, grade of necroinflammation, and use of deferasirox chelation therapy, confirming the clinical usefulness of SDPA R2‐MRI for monitoring iron overload. Magn Reson Med 71:2215–2223, 2014. © 2013 Wiley Periodicals, Inc.